2022
DOI: 10.1021/acs.energyfuels.2c01420
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Organic Structure Carbonization and Organic Pore Destruction at the Overmatured Stage: Implications for the Fate of Organic Pores in Marine Shales

Abstract: To reveal the relationships between kerogen structure variations and the evolution of organic pore (OP) characteristics in overmatured shales, we conducted total organic carbon (TOC) analysis, Raman spectroscopy, Fourier-transform infrared spectroscopy, gas (N2 and CO2) adsorption tests, and field-emission scanning electron microscopy on a high-maturity Silurian shale from South China, alongside its solid residues (kerogen) produced from semi-closed pyrolysis. The results showed that the TOC value of solid res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Shale is composed of various compositions such as OM, brittle minerals, and clay minerals, all of which closely affect pore structure at each scale. ,,,, As shown in Figure a, with the increase in the TOC content, the total PVs of shale samples initially show an increasing trend, followed by a slight decline (Figure a). Similar findings were reported by Milliken et al in the Marcellus shale samples, and they concluded that shale porosity does not consistently increase with rising TOC content; instead, it may decrease at high TOC levels.…”
Section: Discussionmentioning
confidence: 99%
“…Shale is composed of various compositions such as OM, brittle minerals, and clay minerals, all of which closely affect pore structure at each scale. ,,,, As shown in Figure a, with the increase in the TOC content, the total PVs of shale samples initially show an increasing trend, followed by a slight decline (Figure a). Similar findings were reported by Milliken et al in the Marcellus shale samples, and they concluded that shale porosity does not consistently increase with rising TOC content; instead, it may decrease at high TOC levels.…”
Section: Discussionmentioning
confidence: 99%